Comparative study of Shot creep of single-phase titanium alloys in air and neutral gas environment on the test temperature in range from 673 to 1323 K - lev Michailovich Zamaraev; Sergey Smirnov (Fracture and Structural Integrity)
The paper presents the results of comparative studies of short-term creep in tensile tests of the VT1-0 commercially pure titanium (analogue Grade 2 according to ASTM A485) and the VT5-1 alloy (analogue Grade 6 according to ASTM B265) in air and argon. Tests by the Dorn’s method were carried out in a gas-tight chamber under constant pressure. The specimens were heated by passing alternating current. Empirical coefficients are determined in power dependences of the creep rate and the conventional creep strength on test temperature in the range from 673 to 1323 K for argon and air environment and nominal stress ranging between 4.45 and 9.36 MPa. It is found that heating in argon environment, as compared to heating in air, decreases the rate of short-term creep and increases creep strength at identical nominal stresses in the entire range of test temperatures. Calculations demonstrate that the energy of the activation of short-term creep does not depend on test conditions. This indicates that the deformation mechanism is unchanged.